The Voice: A Case Study on Parental Perspectives in Empowering Learners with Special Educational Needs Through Performing Arts Education - Mohamad, Suhaila (Department of Special Education, 2024)
This case study explores parental perspectives on empowering learners with Special Educational Needs (SEN) through performing arts education. It investigates the advantages of performing arts education for learners with SEN and offers recommendations for improvement. It also focuses on understanding parental views on the role of performing arts education in empowering learners with SEN and the benefits derived from such programs. This case study employs a mixed-methods research design, combining quantitative and qualitative approaches through surveys and interviews. The survey method involves administering structured questionnaires to gather numerical data, while interviews provide in-depth insights into parents' perspectives. Triangulation is employed to cross-reference and validate findings using existing literature and theoretical frameworks. The findings highlight parents' perspectives on the importance of performing arts education, including its impact on the personal development, self-expression, and overall well-being of learners with SEN. Recommendations are made to enhance the effectiveness and inclusivity of performing arts education programs based on parental input. This case study contributes valuable insights into performing arts education for learners with SEN from the parents' standpoint, informing future research and practice in this area.